Invertebrados bentónicos del Lago Cote, Costa Rica - Sibaja-Cordero, Jeffrey Alejandro (2008)
Benthic invertebrates of Cote Lake, Costa Rica. The benthic community of Lake Cote, a natural lake in Northwestern Costa Rica, was surveyed in two occasions (1/June and 28/August/2003) in order to determine possible gradients in community composition with depth, following a shore-center transect. In each opportunity, sediment samples were collected with an Ekman dredge at 10 stations ranging in depth from 1 to 12m. Two subsamples (500μm mesh screen), one to study macrofauna and the other to analize sediment characteristics, were collected from each dredge. Meiofauna (between 500 and 63μm mesh screen) was collected with a core (area: 5.3 cm2, depth: 4cm) in the dredge sediment (only in the second visit). Benthic fauna subsamples were preserved in 5% buffered formalin in freshwater stained with Rose Bengal. There was a decrease in temperature with depth, and oxygen levels dropped below 1mg/l below 8m depth. The percent of silt and clay increased with depth, with some exceptions and the center of the lake. A total species richness of 13 taxa was found, including macrofauna (8 taxa) and meiofauna (7 taxa). Lake Cote resembles other tropical lakes in the presence of oligochaete worms and the dipterans Procladius (Chironomidae), Tanytarsus (Chironomidae) and Chaoborus (Chaoboridae). The meiofauna also included some Coleoptera and Acari. Benthic composition was associated with habitat parameters such as substrate granulometry, dissolved oxygen and depth. The low abundance of chironomids may reflect a poor nutrient accumulation on the bottom, caused by the continuous mixing of the water body. Chironomids of the macrofauna were found from the shore to 9m depth. On the other hand, meiofaunal stages were found at less that 9m of depth. Chaoborus larvae were found between 8 and 11m depth, caused by diurnal migration to the deeper zone in the lake. Chaoborus and fish species probably predate on oligochaetes and maintain the low abundance of these worms. The total abundance of the macrofauna reached a maximum at a mid depth, with diversity being greater at shallower depths. The mean density of the macrofauna was 326 individuals per m2, and the mean density of the meiofauna was lower, with two organisms per 10cm2. The distribution of the fauna was clumped, following a gradient with depth. Rev. Biol. Trop. 56 (Suppl. 4): 205-213. Epub 2009 June 30.